ANALISIS PENERAPAN KOMPENSASI KELEBIHAN JAM MENGAJAR DOSEN POLITEKNIK NEGERI UJUNG PANDANG - Andi Muh. Abian Abdi; Syamsuddin; Sumatriani (Prodi Manajemen Universitas Syekh Yusuf Al Makassari Gowa, 2025)
This research was motivated by the unclear regarding the award of honorarium for excess teaching hours at the Ujung Pandang State Polytechnic. This research aims to find out the rules for determining excess teaching hours and honorarium for excess teaching hours for Ujung Pandang State Polytechnic lecturers, to find out their implementation and the conformity of implementation with the rules.The method used is quantitative descriptive analysis. Data collection techniques are documentation and interviews. The results of this research are the rules for determining excess teaching hours and honorarium for excess teaching hours for Ujung Pandang State Poly- technic lecturers: The mandatory teaching load is 9 credits which are charged from practicum courses first; The maximum teaching load is 24 credits; The teaching load that can be paid as excess teaching hours is a maximum of 15 credits; The teaching load paid as excess teaching hours is calculated from theoretical lectures first; Lecturers who are continuing their studies do not have a mandatory teaching load. The Implementation for determining excess teaching hours for Ujung Pandang State Polytechnic lecturers is to calculate the number of credits taught in regular D3 and D4 classes. The maximum number is 24 minus 9 credits. The difference is the excess teaching hours expressed in credit units. The excess teaching hours are first calculated from the credits for theory courses. If the number of excess teaching hours is less than the number of credits for theory courses, then the remainder is taken from the credits for practical courses. The unit uses theory credits and practical hours. The implementation of determining the honorarium for excess teaching hours for Ujung Pandang State Polytechnic lecturers can clearly be calculated using mathematical formulas. The implementation of determining excess teaching hours and honorarium for excess teaching hours for Ujung Pandang State Polytechnic lecturers is in accordance with the applicable regulations